MENINGKATKAN KEMAMPUAN SPATIAL SENSE DAN PEMECAHAN MASALAH MATEMATIK SISWA SMA MELALUI PENDEKATAN BERBASIS MASALAH - Nurkholis, Encep (LPPM Universitas Bina Bangsa, 2022)
This paper presents the findings from a pretest-posttest experimental control group design conducted by using problem based learning assisted with computer program to investigate students’ spatial sense and problem solving abilities.The study involved 72 grade-10 students in Karangununggal. The instrumens in this study are spatial sense and mathematical problem solving abilities tests, and opinion scale. The study found that: a) The problem based learning assisted with computer program was able to improve students’ spatial sense and mathematical problem solving abilities much better than the conventional approach. Spatial sense and mathematical problem solving abilities of students taught by using problem based learning assisted with computer program were classified as fairly good, whereas those abilities of students taught by conventional teaching were classified as mediocore. Nevertheless, there were no difference on the gain of those students’abilities of the both classes; b) There was high association between spatial sense and mathematical communication abilities; c) Students performed positive opinion and enthusiastic toward problem based learning assisted with computer program